Cloud Condensation Nuclei in Fire-3 (2000)
The centerpiece of this research was the cloud condensation nuclei (CCN) measurements of the Desert Research Institute (DRI) CCN spectrometers on board the NCAR C-130 aircraft during the Arctic Cloud Experiment (ACE) in May, 1998. These instruments operated successfully throughout all eight 10-hour research flights based in Fairbanks and the two ferry flights between Colorado and Fairbanks. Within a few months of completion of ACE the CCN data was edited and put into the archives. A paper was completed and published on the CCN climatology during the previous two FIRE field projects-FIRE 1 based in San Diego in June and July, 1987 and ASTEX based in the Azores Islands in June, 1992. This showed distinct contrasts in concentrations and spectra between continental and maritime CCN concentrations, which depended on air mass trajectories. Pollution episodes from Europe had distinct influences on particle concentrations at low altitudes especially within the boundary layer. At higher altitudes concentrations were similar in the two air mass regimes. Cloudier atmospheres showed lower concentrations especially below the clouds, which were a result mostly of coalescence scavenging.